PERLINDUNGAN HUKUM TERHADAP KORBAN KEJAHATAN PEMERKOSAAN YANG TERJADI DI KOTA SAMARINDA - MUHAMMAD FACHRI PUTRA ADILLIN (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACTThis Legal Writing aims to know about the legal protection afforded to victims of crime of rape and punishment given to perpetrators of rape crimes. Efforts to protect victims of rape in the criminal justice system can not be separated from the participation of the parties involved in the criminal justice system, even though the rules on the protection of victims have been regulated in such legislation. It will not work effectively and maximally when in practice the elements that can support the achievement of victim protection are not mutually supportive We may also recognize the existence of criminal sanctions in the Criminal Code in article 285 up to article 288. Keywords: Legal Protection, Crime, Rape.